The experiences and needs of HIV/AIDS counsellors at Settlers Hospital, Grahamstown - Nulty, Maria (Rhodes University, Faculty of Humanities, Department of Psychology, 2004)
Cognisant of the fact that counselling has become an essential aspect of dealing with HIV/AIDS in South Africa, the researcher aimed to explore the stressors experienced by HIV/AIDS counsellors. It was envisioned that the results obtained would both help to improve the counselling services provided at Settlers Hospital, and assist other organisations to do so. The research focused on how the participants dealt with the dual roles of non-directive listening and the more prescriptive advice-giving, the stressors they experienced and the support structures they had, or needed, to assist them in being more effective HIV/AIDS counsellors. The sample consisted of four HIV/AIDS counsellors working at Settlers Hospital, Grahamstown. The co-ordinator of HIV/AIDS at the hospital was interviewed for collateral information. A qualitative, multiple case study was undertaken. In-depth, semi-structured interviews were used to collect the data which were recorded and transcribed and then constructed into coherently organised personal narratives of each participant's experiences. A composite description of all the results was arrived at through the use of a reading guide which reduced the data into a thematic content analysis. The analysed data served to present an understanding of the counsellors' experiences and to enable recommendations to be made which could assist them in pursuing their work more effectively. The findings of this study indicate that HIV/AIDS counselling is an emotionally stressful occupation. Contributory factors include the twofold role of promoting prevention and serving as empathic listeners. Other stressors derive from issues of confidentiality and stigma concerning HIV/AIDS, counsellors' identification with clients' experiences and the demographics of HIV/AIDS in South Africa. Situational stressors which arise from working as both nurses and counsellors in a public health institution were also identified. Recommendations are made to alleviate the counsellors' stress in the form of facilitated emotional support groups, professional supervision, managerial support to improve the working environment, and ongoing in-service training.
Keywords: AIDS (Disease) -- Patients -- Counseling of -- South Africa -- Eastern Cape; HIV-positive persons -- Counseling of -- South Africa -- Eastern Cape; Counselors -- South Africa -- Eastern Cape; Counselors -- Supervision of -- South Africa -- Eastern Cape; Counselors -- Training of -- South Africa -- Eastern Cape